Revitalisasi Kelembagaan Madrasah Diniyah di Pamekasan - Mohammad Thoha; R. Taufikurrahman (Research Institute and Community Engagement of IAIN MADURA, 2022)
Madrasah diniyah grows and develops with the community. Its existence illustrates the level of community diversity. Along with the shift in the mindset of the community, the sustainability of the madrasah diniyah is threatened because it is seen as a